2021
DOI: 10.1515/rams-2021-0031
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of cement-stabilized materials using 100% mixed recycled aggregates from perspectives of mechanical properties and microstructure

Abstract: The research on the highly efficient reutilization of mixed recycled aggregates (MRA) produced from construction and demolition waste has attracted significant attention globally. In this study, the feasibility of using 100% MRA in cement-stabilized materials was investigated. The mechanical properties and microstructures of cement-stabilized MRA (CSMRA) materials containing 100% MRA were systematically examined through unconfined compressive strength (UCS) test, indirect tensile strength (ITS) test, drying sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…The crushed C&DW particles are mainly composed of concrete, mortar, bricks, glass, and wood pieces and can be used as mixed coarse recycled aggregate (MCRA) [ 7 , 8 , 9 ]. The physical properties of MCRA are complex owing to its various components.…”
Section: Introductionmentioning
confidence: 99%
“…The crushed C&DW particles are mainly composed of concrete, mortar, bricks, glass, and wood pieces and can be used as mixed coarse recycled aggregate (MCRA) [ 7 , 8 , 9 ]. The physical properties of MCRA are complex owing to its various components.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the small particle size, the packing effect occurs, which reduces the overall porosity and optimizes the pore structure and the performance of the interfacial transition zone. Due to the small particle size, the packing effect occurs, which reduces the overall porosity and optimizes the pore structure and the performance of the interfacial transition zone [25][26][27][28][29][30][31][32]. Second, in the mixing process of the mixture, because there are many pores in RA, absorbing more water is conducive to the hydration process of the water-stable specimen in the health period, generating more cement hydration products and improving the cohesion of the mixture [29].…”
Section: Analysis Of Thementioning
confidence: 99%
“…Recently, numerous laboratory studies and field trials have shown that recycled aggregate can totally or partially replace natural aggregates in road construction. Potential savings in cost and time of recycling of construction and demolition debris have made the use of RCA an attractive alternative to the highway engineer as it contributes to more sustainability in the construction [6]. Although many authors have studied the possibility of using RCA in applications, there are a few researches on the properties and mechanical behavior of mixtures treated with cement when used as road subbases or base in paving, roads because of these reasons: improving the workability of road materials, increasing the strength of the mixture, enhancing the durability, increasing the load spreading capacity.…”
Section: Introductionmentioning
confidence: 99%